Perception of Malaysian dental practitioner on the provisional COVID-19 guidelines in the dental practice : a cross-sectional study - Nurul Haini Najwa Mohamd Mahmod,; Raja Nur Nabiha Raja Amir Hamzah,; Nor Faharina Abdul Hamid,; Azlan Jaafar, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Following the COVID-19 outbreak, the World Health Organization issued provisional guidelines to address considerations for essential oral health services in the pandemic situation. Compliance with the guidelines is essential to curb the potential spread of infection within a dental practice. This study aimed to assess the perception of Malaysian dental practitioners towards exercising the provisional COVID-19 dental practice guideline during the early phase of the pandemic. A self-administered questionnaire of a structured type consisting of demographic information and dentist perceptions of the provisional guidelines of dental care during the COVID-19 outbreak was distributed online from May 2021 until August 2021 through various social networking platforms among dental practitioners working at different healthcare sectors in all states in Malaysia. A total of 468 dental practitioners responded to this study. More than threequarters of the respondents were working in public dental care facilities (76.3%, n=357). The majority of respondents adhered to the provisional guidelines issued during the pandemic outbreak and exhibited a change in standard clinical practice (p<0.001). Dental practitioners working in public sectors perceive that swab tests prior to dental appointments should be mandatory, the reopening of dental clinics increases the risk of spread and the provisional guidelines of COVID-19 in dental practice will be changed in the future compared to private dental practitioners (p<0.001). The majority of dental practitioners in Malaysia have complied with the provisional guidelines imposed by the health bodies. As the COVID-19 virus will persist and become endemic in our communities, it is important to balance the safety issue and patient oral health needs.